2008
DOI: 10.1073/pnas.0710947105
|View full text |Cite
|
Sign up to set email alerts
|

Noncanonical role of Hox14 revealed by its expression patterns in lamprey and shark

Abstract: Hox genes are arranged in uninterrupted clusters in vertebrate genomes, and the nested patterns of their expression define spatial identities in multiple embryonic tissues. The ancestral Hox cluster of vertebrates has long been thought to consist of, maximally, 13 Hox genes. However, recently, Hox14 genes were discovered in three chordate lineages, the coelacanth, cartilaginous fishes, and amphioxus, but their expression patterns have not yet been analyzed. We isolated Hox14 cDNAs from the Japanese lamprey and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
53
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(58 citation statements)
references
References 35 publications
4
53
1
Order By: Relevance
“…These data confirm that Hoxa14 is potentially functional. PG-14 genes have also been found in two other cartilaginous fishes, the cloudy catshark, Scyliorhinus torazame (HoxD14) (48), and the elephant shark (HoxD14, as well as HoxA14 and HoxC14 pseudogenes) (33). Moreover, it was shown that the Japanese lamprey, a jawless vertebrate, also possesses a Hox14 gene (48), suggesting that PG-14 existed before the divergence of lampreys and gnathostomes.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…These data confirm that Hoxa14 is potentially functional. PG-14 genes have also been found in two other cartilaginous fishes, the cloudy catshark, Scyliorhinus torazame (HoxD14) (48), and the elephant shark (HoxD14, as well as HoxA14 and HoxC14 pseudogenes) (33). Moreover, it was shown that the Japanese lamprey, a jawless vertebrate, also possesses a Hox14 gene (48), suggesting that PG-14 existed before the divergence of lampreys and gnathostomes.…”
Section: Discussionmentioning
confidence: 88%
“…PG-14 genes have also been found in two other cartilaginous fishes, the cloudy catshark, Scyliorhinus torazame (HoxD14) (48), and the elephant shark (HoxD14, as well as HoxA14 and HoxC14 pseudogenes) (33). Moreover, it was shown that the Japanese lamprey, a jawless vertebrate, also possesses a Hox14 gene (48), suggesting that PG-14 existed before the divergence of lampreys and gnathostomes. Expression analysis of the lamprey and catshark Hox14 genes by in situ hybridization indicated that the genes did not show a predicted posterior axial pattern of Hox expression; rather, the genes showed a noncanonical expression pattern in the gut that overlapped with that of Hox13, implying that the PG-14 genes may have arisen as a gene duplicate of Hox13, complete with gut-specific regulatory sequences (48).…”
Section: Discussionmentioning
confidence: 88%
“…Despite the incompleteness of Hox-e, -ζ, -η, and -θ loci, there is sufficient evidence that Japanese lamprey contains at least six Hox clusters. The singleton Hox4 gene in the Hox-η locus (Hox-η4) is unique in that it comprises four coding exons compared with two exons in most Hox genes and three exons in Hox13 and Hox14 genes (5,(24)(25)(26). The coding sequence of the singleton Hox4 gene in Hox-θ locus (Hox-θ4) is highly similar to Hox-η4, but its first two exons are not identifiable and the last exon contains a premature stop codon.…”
Section: Resultsmentioning
confidence: 99%
“…It is not clear whether these ancient genes were redundant genes that were retained for varying periods and then lost, or whether they performed some unique functions that have been perturbed in the lineages that have lost them. There is evidence to suggest that 1 of the ancient Hox genes, HoxD14, which has been lost in bony vertebrates, had a unique expression pattern in cartilaginous fishes; it is expressed in a restricted cell population in the hindgut, but not in the central nervous system, somites, or fin buds/folds that are known to express Hox genes (29). Consequent to its loss in bony vertebrates, the function performed by this gene in cartilaginous fishes must have been perturbed in bony vertebrates.…”
Section: Resultsmentioning
confidence: 99%